ANALISIS KEBUTUHAN MEDIA PEMBELAJARAN IPAS PADA MATERI PANCA INDERA MANUSIA DI SEKOLAH DASAR - Farulyan, Neska; Fitria Nurulaeni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to analyze the need for science and technology learning media on human five senses material in elementary schools. The research used a qualitative approach with a case study design carried out in five elementary schools in the Cikembar District cluster, Sukabumi Regency. Research subjects included 5 class III teachers and 139 students. Data collection techniques were carried out through interviews and distributing needs analysis questionnaires prepared using a Likert scale. The results of the research show that teachers have a very positive view of the use of learning media because it is able to increase students' interest in learning, activeness and understanding of concepts and helps convey learning objectives more clearly. However, the availability of science and technology learning media in schools is still limited and not completely attractive. Meanwhile, the results of the analysis of student needs show that students have a high interest in learning supported by visual and interactive media, such as pictures, videos and animations, because it makes it easier to understand concrete material. Based on these findings, it can be concluded that the development of concrete, visual and interactive science learning media is very necessary to support the learning characteristics of elementary school students and improve the quality of the scienceas learning process and outcomes.